Desida Cronica. La crisis del agua in El Salvador - Alvarez y Alvarez, Luis (Spain : CDC ; Witness, 2009)
While there is no shortage of water in El Salvador, almost 60% of the rural population has no access to a reliable water source, forcing women and girls to walk long distances and pay high prices to obtain water of dubious quality. In cities, water is almost never lacking in wealthy neighborhoods, where swimming pools are common, while in poor areas where water is available only a few hours a day or during the night, the price can reach 10 % of a household's income. Through everyday stories, "Chronic Neglect" documents the failures of an unregulated system which rewards waste and allows unequal access to water, a situation that demands prompt attention to the human right to water in El Salvador.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films